Sistem Pengendalian Internal Pemerintah Sebagai Variabel Moderasi; Dalam Hubungan Peran Auditor Internal Terhadap Kualitas Penyajian Laporan Keuangan - Semy Pesireron; Mis Fertyno Situmeang (Univiversitas Dr. Djar Wattiheluw, 2024)
As a moderating variable, the research objective is to empirically test the influence on the quality of financial reports and the influence of the government's internal control system. The type of research is the causal relationship with sampling technique, by using purposive sampling. The survey sampling method is used in data collection and data analysis technique through Moderate Regression Analysis (MRA) with a significant degree 0.05. The result of the research is to prove the role of the government's internal auditor does not significantly affect the quality of the Maluku Provincial Government's financial statement. Furthermore, the government's internal system has a significant effect on the relationship between the role of the government's internal auditor, but it has no significant effect on the quality of the Maluku Provincial Government's financial report.